PENGEMBANGAN MEDIA AUDIO VISUAL BERBANTUAN GOOGLE DRIVE PADA PEMBELAJARAN TEMATIK - Fadilah Azzahra; Damanhuri; Reksa Adya Pribadi; Muhammad Taufik (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The goal of this study was to assess the viability of using audio-visual learning media to promote students’ learning, particularly in thematic learning, as well as students’ responses to the media generated by researchers. The research approach was Research and Development (R&D) following the 4D (Four-D) development model of define, design, develop, and disseminate. Based on the opinions of teachers, media professionals, and material experts, the results demonstrated the viability of audio-visual media. Each teacher had an average score of 87.5%, while media specialists received an average score of 92.3% and material experts received an average score of 79.2%. Following that, the students' reactions to the media employed in the learning process were 96.9%. Based on the findings of these investigations, it was concluded that this research created audio-visual media products in the form of learning films in thematic learning for grade V Elementary School using Google Drive. The teacher and media expert validation results fell into the "Very Eligible" group, while material experts fell into the "Eligible" category. The "Very Good" category included evaluations of students’ responses. As a result, the product was stated to be suitable for use as a learning medium.